Biological control of Erwinia mallotivora, the causal agent of papaya dieback disease by indigenous seed-borne endophytic lactic acid bacteria consortium - Mohd Hashim, Amalia; Mohd Jaini, Mohammad Fahrulazri; Mohd Taha, Mariam Dayana; Abdul Rahim, Raha; Saidi, Noor Baity; Md Shah, Umi Kalsom (Public Library of Science, 2019)
Dieback disease caused by Erwinia mallotivora is a major threat to papaya plantation in Malaysia. The current study was conducted to evaluate the potential of endophytic lactic acid bacteria (LAB) isolated from papaya seeds for disease suppression of papaya dieback. Two hundred and thirty isolates were screened against E. mallotivora BT-MARDI, and the inhibitory activity of the isolates against the pathogen was ranging from 11.7–23.7 mm inhibition zones. The synergistic experiments revealed that combination of W. cibaria PPKSD19 and Lactococcus lactis subsp. lactis PPSSD39 increased antibacterial activity against the pathogen. The antibacterial activity was partially due to the production of bacteriocin-like inhibitory substances (BLIS). The nursery experiment confirmed that the application of bacterial consortium W. cibaria PPKSD19 and L. lactis subsp. lactis PPSSD39 significantly reduced disease severity to 19% and increased biocontrol efficacy to 69% of infected papaya plants after 18 days of treatment. This study showed that W. cibaria PPKSD19 and L. lactis subsp. lactis PPSSD39 are potential candidate as biocontrol agents against papaya dieback disease.